Volumetric MRI study of orbito-frontal cortex and thalamus in obsessive-compulsive personality disorder - Atmaca, Murad; Korucu, Tuba; Tabara, Muhammed Fatih; Yildirim, Hanefi; Kilic, Mehmet Caglar (Elsevier Sci Ltd, 2019)
Objectives: Obsessive compulsive personality disorder (OCPD) is currently thought to bear a close relationship with obsessive-compulsive disorder (OCD), and other compulsive disorders such as eating disorder and autistic spectrum disorder, as well as with the personality disorders, focusing on some important dimensions like phenomenology, heritability, environmental risk factors, comorbidity, course of illness, neurocognitive endophenotypes, and treatment response. In the present study, when we have taken into consideration the knowledge aforementioned, we aimed to examine OFC and thalamus volumes in patients with OCPD. Methods: We comparatively measured orbito-frontal cortex (OFC) and thalamus volumes of patients with OCPD and healthy control subjects. Results: Patients with OCPD had considerably smaller left and right OFC volumes compared to those of healthy control subjects. We also found that thalamus volumes of patients were statistically significantly greater than those of healthy comparisons for both sides of region of interest. Conclusions: We consider that volumetric alterations determined in the present study may be involved in the pathophysiology of the OCPD, considering that OCPD might be related to OCD spectrum disorders neuroanatomically. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: MRI; Volume; OCPD; OFC; Thalamus